Improving transition to adult healthcare for young people with cystic fibrosis: A systematic review. (September 2017) - Coyne, Imelda; Sheehan, Aisling M; Heery, Emily; While, Alison E
As survival increases worldwide, large numbers of young people will need to transition from child to adult cystic fibrosis (CF) services. Little is known about the best method for transitioning patients with CF and which transition programmes yield better outcomes. This paper provides a systematic review of the empirical literature on the outcomes and experiences of transition for young people with CF. Outcomes data were subject to a narrative synthesis and a thematic synthesis of experiences data. Structured transition programmes were associated with increased satisfaction, discussions about transition, self-care and self-advocacy skills, more independence, lower anxiety, and increased self-management and parent management of physiotherapy and nutritional supplementation. Young people's concerns included leaving behind previous caregivers, differences in care provision and infection risks. Lack of preparation was a consistent theme. The two most useful aspects of transition programmes were meeting the adult doctors/CF specialist nurse/team and visiting the adult centre. Young people want education about the differences between services, implications of their condition and self-care management. Structured transition programmes appear to impact positively on experiences but the contribution of the different components of transition programmes is unclear. The absence of high-quality studies indicates the need for more well-designed research.